A phase 2 study of the bivalent VLP norovirus vaccine candidate in older adults; impact of MPL adjuvant or a second dose. Issue 36 (10th August 2020) - Treanor, John; Sherwood, Jim; Cramer, Jakob P.; Le Cam Bouveret, Nancy; Lin, Stella; Baehner, Frank; Borkowski, Astrid; ,
Highlights: Dose and adjuvant confirmation trial in adults 60–102 years with young adult cohort. A single adult dose was as safe and immunogenic in older adults as young adults. No immunologic benefit was gained by either a second dose or including an adjuvant. Induced antibodies remained above baseline for at least one year after vaccination. A strong response to GII.4 heterovariants was observed in adults of all ages. Abstract: Introduction: Acute norovirus gastroenteritis causes significant morbidity and in uncommon cases fatality in older adults. We investigated the safety and immunogenicity of bivalent virus-like particle (VLP) vaccine candidate formulations with and without monophosphoryl lipid A (adjuvant MPL) in this population. Methods: In this phase II, double-blind, controlled trial 294 healthy adults, ≥ 60 years of age, were randomized (1:1:1:1) to four groups to receive one or two intramuscular immunizations 28 days apart, with 26 18–49 year-old controls who received one MPL-free dose. One-dose groups received placebo on Day 1. Vaccine formulations contained 15 μg GI.1 and 50 μg GII.4c VLP antigens and 500 μg Al(OH)3, with or without 15 μg MPL. We measured histo-blood group antigen blocking (HBGA) antibodies and ELISA Ig at Days 1, 8, 29, 57, 211 and 393, and avidity indices and cell-mediated immunity (CMI). Solicited local and systemic adverse events (AE) were assessed for 7 days and unsolicited AEs for 28 days after each injection. Results: After one dose HBGA antibodies to both VLP antigens increased with similar kinetics and magnitude in all groups; geometric mean titres (GMTs) persisted above baseline through Day 393. GMTs were similar across age strata (18–49, 60–74, 75–84 and ≥ 85 years of age) and unaffected by a second vaccination or MPL. Total Ig showed similar responses. No clinically relevant differences or changes in avidity or CMI were observed between formulations. Both formulations were well tolerated with no vaccine-related SAEs, the most frequent AEs being mild injection site pain and fatigue. Conclusions: Adults over 60 years of age displayed no safety concerns and had similar immune responses to the norovirus VLP vaccine candidate as younger adults, unaffected by increasing age, a second dose or inclusion of MPL. This data supports the further development of the MPL-free vaccine candidate for older adults.